2009
DOI: 10.1002/jor.20958
|View full text |Cite
|
Sign up to set email alerts
|

Orderly osteochondral regeneration in a sheep model using a novel nano‐composite multilayered biomaterial

Abstract: The objective of this article was to investigate the safety and regenerative potential of a newly developed biomimetic scaffold when applied to osteochondral defects in an animal model. A new multilayer gradient nano-composite scaffold was obtained by nucleating collagen fibrils with hydroxyapatite nanoparticles. In the femoral condyles of 12 sheep, 24 osteochondral lesions were created. Animals were randomized into three treatment groups: scaffold alone, scaffold colonized in vitro with autologous chondrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
158
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(171 citation statements)
references
References 32 publications
7
158
0
4
Order By: Relevance
“…This observation is in line with other studies that demonstrated that differences in DNA levels and tissue formation due to different initial cell densities disappear during long-term culture (Hansen et al, 2013;Kon et al, 2010). However, other studies reported beneficial effects of increased cell densities using higher initial cell densities compared to the current study (Chen et al, 1997;Puelacher et al, 1994;Talukdar et al, 2011).…”
Section: Discussionsupporting
confidence: 57%
“…This observation is in line with other studies that demonstrated that differences in DNA levels and tissue formation due to different initial cell densities disappear during long-term culture (Hansen et al, 2013;Kon et al, 2010). However, other studies reported beneficial effects of increased cell densities using higher initial cell densities compared to the current study (Chen et al, 1997;Puelacher et al, 1994;Talukdar et al, 2011).…”
Section: Discussionsupporting
confidence: 57%
“…Maioregen (Fin-Ceramica Faenza S.p.A., Faenza-Italy) is a thick, nanostructured biomimetic collagen and hydroxyapatite scaffold used for treatment of large osteochondral lesions. As in the AMIC technique, cell migration from the surrounding host bone and bone marrow is required in order to colonise the scaffold and achieve functional repair (Kon et al, 2010a;2010b). Osteochondral morselised grafts have been proposed as a "paste" without any scaffold for one-stage repair of full thickness articular cartilage lesions and osteochondral defects, both in animal and human studies (Stone et al, 2006;Mahadev et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the quality of cartilage regenerated in an empty osteochondral defects is of poor quality. Previous reports indicate that in empty osteochondral control defects neither bone nor cartilage is formed; the repair tissue formed is fibrous or a mixed-type fibrocartilage tissue with poor integration with the surrounding cartilage [44,[54][55]. In our study we used a gradient 3D osteochondral scaffold that encapsulated raw materials, chondrodroitin sulfate and β tricalcium phosphate.…”
Section: Future Perspectivementioning
confidence: 99%